Peran Influencer Marketing dalam Mempengaruhi Loyalitas Merek - Razati, Girang; Aripin, Arip Nur; Hurriyati, Ratih (Business Education Program of Universitas Pendidikan Indonesia, 2021)
This study aims to determine the description of influencer marketing and brand loyalty as well as the influence of influencer marketing on brand loyalty to Nike customers in the Indonesia Sneaker Team Facebook group, which amounts to 85 respondents. The questionnaire was used as a research instrument to collect data from respondents. The design and method of this research is an explanatory survey with a quantitative approach. The analysis technique used is the verification technique using simple linear regression analysis. Based on the research results, there is a positive and significant influence between influencer marketing on brand loyalty in Nike customers. Verificatively, the data shows that influencer marketing has a good effect on brand loyalty.